Cultivating sustainability: Adoption and intensity of soil fertility management technologies among rural farms in Zambia - Louis Chikopela; Thomson H. Kalinda; John N. Ng'ombe; Elias Kuntashula (World Development Sustainability)
Despite the numerous advantages of soil fertility management (SFM) practices and substantial investments to promote adoption, uptake of these technologies remains low across sub-Saharan Africa. We study the adoption and intensity of key SFM practices - improved fallow, animal manure, compost, crop residue retention, minimum tillage, inorganic fertilizer, and intercropping among rural farmers in Zambia. Data from 1234 rural farms and the multivariate probit (MVP) and generalized Poisson regression models are used. The MVP model highlights interconnections among practices, emphasizing the need for integrated interventions. Socio-demographics like gender, age, education, and household labor availability significantly influence adoption of SFM practices. Farm characteristics including experience, land ownership, livestock, and off-farm income also play pivotal roles. Accessibility of information via phones, radio, and farmer groups emerged as a crucial enabler, while extension services, credit, and proximity to markets and roads shape adoption decisions. Results indicate education, household labor, off-farm income, and group membership drive intensity of adoption. Extension contacts, training, and agro-ecological region location also affect intensity with regional variations. Key policy implications emerge. First, the complementarities among practices underscore the need for holistic strategies recognizing these synergies. Second, enhancing education specifically for younger farmers can promote adoption of SFM technologies by increasing knowledge. Third, spurring farmer groups facilitates knowledge exchange, input access, and collaborative adoption. Fourth, strategic extension services and training programs are vital to address knowledge gaps for sustained adoption. Overall, this study provides insights to guide policies for promoting SFM practices among rural farms.